2011
DOI: 10.1002/jwmg.132
|View full text |Cite
|
Sign up to set email alerts
|

Using a general index approach to analyze camera‐trap abundance indices

Abstract: The lack of variance estimates constrain the utility of abundance indices calculated from camera‐trap data. We adapted a General Index model, which allows variance estimation, to analyze camera‐trap observations of feral pigs (Sus scrofa) for population monitoring in a tropical rainforest. We tested whether the index would respond to population manipulation, and found that it decreased by 57% following removal of 24 pigs and remained low in the following period. Our method is useful for monitoring other large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 29 publications
0
50
0
Order By: Relevance
“…Instead, this study generally showed the weakest results of all three. As suggested by Bengsen et al (2011) that «placing camera traps in a non-random way is not necessarily an issue as it is the animal population within an area that is the subject of sampling by observation stations, not the area itself».…”
Section: Discussionmentioning
confidence: 99%
“…Instead, this study generally showed the weakest results of all three. As suggested by Bengsen et al (2011) that «placing camera traps in a non-random way is not necessarily an issue as it is the animal population within an area that is the subject of sampling by observation stations, not the area itself».…”
Section: Discussionmentioning
confidence: 99%
“…This abundant activity, combined with the fact that deer mice are known pests of many orchard crops (e.g., almonds; Pearson et al 2000), encouraged us to test these same rodenticide baits on deer mice as well as roof rats. Given the large number of studies validating the use of a general index to monitor population changes (e.g., Bengsen et al 2011;Engeman and Whisson 2006;Latham et al 2012), we have no reason to believe that the same index of activity would not effectively represent changes in deer mouse populations pre-and posttreatment.…”
Section: Indexing Trialsmentioning
confidence: 99%
“…To be practical, such an index should be simple and easily applied in the field, while being sensitive to population changes. A general paradigm with good quantitative properties for indexing animal populations has been developed and applied to many species using many observation methods (e.g., European rabbit, Oryctolagus cuniculus [Latham et al 2012] and wild pigs, Sus scrofa [Engeman et al 2007;Bengsen et al 2011]). In particular, this approach has served well for rodents (Engeman and Whisson 2006;Whisson et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Size-wise, camera stations are probably most similar to the short-length tracking plots. Despite relatively high initial costs for cameras, this method opens the possibility of reduced labor cost for monitoring wildlife abundance (Bengsen et al 2011;Silveira et al 2003;Rowcliffe et al 2008). The use of cameras has obvious advantages in efficiency over conventional survey techniques (like tracking plots): fewer field visits and reduced staff labor time and more data resulting from continued activation and reduced downtime from adverse weather conditions (Minta and Mangel 1989;De Bondi et al 2010;Meek et al 2012).…”
Section: Camera Trapsmentioning
confidence: 99%
“…To produce an abundance estimate from occupancy data requires a variety of often hard-to-meet assumptions, including population closure, and each map unit with swine is accurately assessed as having them and that distinct individuals cannot be detected in >1 unit during the observation session. Even if assumptions are met, occupancy methods do not appear well-suited for gregarious (Bengsen et al 2011) and/or ubiquitous species in areas where they are wellestablished, because even large changes in abundance potentially could go undetected between monitoring sessions. Most likely, this method would primarily find utility in assessing swine populations at the leading edges of range expansion (or perhaps contraction).…”
Section: Using Plot Occupancy For Abundance Estimationmentioning
confidence: 99%